2013
DOI: 10.1039/c3tb20608d
|View full text |Cite
|
Sign up to set email alerts
|

Controlled in situ synthesis of surface functionalized BaSO4 nanoparticles for improved bone cement reinforcement

Abstract: Controlled in situ synthesis of surface functionalized BaSO 4 nanoparticles is achieved by using a difunctional molecule to modulate the growth of nanoparticles coupled with in situ generation of SO 4 2À under mild conditions. Such BaSO 4 nanoparticles with surface vinyl groups reinforce the PMMA bone cement better than conventional BaSO 4 particles. † Electronic supplementary information (ESI) available: Details of the experiment, XRD, FTIR, TEM, SEM, pH change with reaction time, the equation for simulation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…The volume shrinkage, as a major drawback of PMMA bone cement, has been tackled by its expansion property as the introduction of the expandable substances into the solid or liquid phase. The solid phase modification of PMMA bone cement mainly focused on the improvement of the hydrophilicity like hydrophilic bone cements (HBCs),3,4 and also the additives of the filling materials, such as barium sulfate, bioactive hydroxyapatite (HA) nanoparticles and BMP 2,5–7 could reduce the shrinkage of the matrix. In our previous studies, PAAS fibers and poly(methyl methacrylate‐ co ‐acrylic acid) [P(MMA‐AA)] microspheres were incorporated into the solid phase of commercial PMMA bone cement to eliminate its shrinkage 8,9.…”
Section: Introductionmentioning
confidence: 99%
“…The volume shrinkage, as a major drawback of PMMA bone cement, has been tackled by its expansion property as the introduction of the expandable substances into the solid or liquid phase. The solid phase modification of PMMA bone cement mainly focused on the improvement of the hydrophilicity like hydrophilic bone cements (HBCs),3,4 and also the additives of the filling materials, such as barium sulfate, bioactive hydroxyapatite (HA) nanoparticles and BMP 2,5–7 could reduce the shrinkage of the matrix. In our previous studies, PAAS fibers and poly(methyl methacrylate‐ co ‐acrylic acid) [P(MMA‐AA)] microspheres were incorporated into the solid phase of commercial PMMA bone cement to eliminate its shrinkage 8,9.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that the addition of additives into PMMA bone cements would decrease the mechanical property [32,33]. In our group’s previous study, the compressive strength also decreased with addition of magnesium balls [33].…”
Section: Discussionmentioning
confidence: 71%
“…The molar ratio of MSAH/BaCl 2 is set between 0 and 0.128 referring to our previous work. 35 The morphology of the BaSO 4 particles synthesized with different combinations of pre-decomposition time and MSAH/BaCl 2 molar ratio are systematically presented in Fig. 1-6 and Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…In our previous work, a new strategy to achieve the controlled synthesis of surface functionalized BaSO 4 nanoparticles under mild conditions was developed. 35 The in situ generation of SO 4 2À was realized by the thermal decomposition of K 2 S 2 O 8 in an aqueous, basic solution. Additionally, the difunctional molecule, 2-(methacryloyloxy)ethyldimethyl-(3-sulfopropyl) ammonium hydroxide (MSAH) was used as a surface modication agent.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation